2013
DOI: 10.1161/circulationaha.112.001170
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Infective Endocarditis

Abstract: Background-Because of the nephrotoxic effects of aminoglycosides, the Danish guidelines on infective endocarditis were changed in January 2007, reducing gentamicin treatment in enterococcal infective endocarditis from 4 to 6 weeks to only 2 weeks. In this pilot study, we compare outcomes in patients with Enterococcus faecalis infective endocarditis treated in the years before and after endorsement of these new recommendations. Methods and Results-A total of 84 consecutive patients admitted with definite left-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 51 publications
3
38
0
4
Order By: Relevance
“…Wskazania do stosowania aminoglikozydów i schemat leczenia uległy zmianie. Leków tych nie zaleca się w gronkowcowym NVE, ponieważ nie potwierdzono korzyści klinicznych takiego postępowania, a leki z tej grupy cechują się nefrotoksycznością [128]; w przypadku istnienia innych wskazań aminoglikozydy należy stosować w pojedynczej dawce dobowej w celu zmniejszenia nefrotoksyczności [129]. 2.…”
Section: Zasady Ogólneunclassified
See 1 more Smart Citation
“…Wskazania do stosowania aminoglikozydów i schemat leczenia uległy zmianie. Leków tych nie zaleca się w gronkowcowym NVE, ponieważ nie potwierdzono korzyści klinicznych takiego postępowania, a leki z tej grupy cechują się nefrotoksycznością [128]; w przypadku istnienia innych wskazań aminoglikozydy należy stosować w pojedynczej dawce dobowej w celu zmniejszenia nefrotoksyczności [129]. 2.…”
Section: Zasady Ogólneunclassified
“…Ponadto jest to schemat terapii z wyboru w leczeniu IZW wywołanego przez E. faecalis z HLAR. Po drugie, zaleca się, aby całkowitą dawkę gentamicyny podawać w pojedynczej dawce, zamiast 2 lub 3 dawek podzielonych, a czas leczenia w przypadku IZW wywołanego przez szczepy E. faecalis bez HLAR, można bezpiecznie skrócić z 4-6 tygodni do 2 tygodni, zmniejszając odsetek powikłań nefrotoksycznych do bardzo niskiego poziomu [129,186,187].…”
Section: Enterococcus Sppunclassified
“…In this issue of Circulation, Dahl et al 8 report on the efficacy and safety of ampicillin plus short-course gentamicin for treating non-HLAR EFIE in Denmark. 8 The rationale of the study relies on the good results reported in 2002 in Sweden by Olaison and Schadewitz,9 who performed a 5-year prospective study including 93 cases of EFIE.…”
mentioning
confidence: 99%
“…8 The rationale of the study relies on the good results reported in 2002 in Sweden by Olaison and Schadewitz,9 who performed a 5-year prospective study including 93 cases of EFIE. Clinical cure was achieved in 75 episodes (81%) that had been treated with a median 2-week course of aminoglycosides.…”
mentioning
confidence: 99%
See 1 more Smart Citation